Access to Infrastructure and Women's Time Allocation: Evidence and a Framework for Policy Analysis - Pierre-Richard Agenor; Otaviano Canuto (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper studies the interactions between access to infrastructure, women's time allocation, and economic growth in developing countries. The first part provides a review of the evidence on the impact of poor infrastructure on women's ability to allocate their time to productive activities. The second part presents a quantitative framework for policy analysis, in the form of a gender-based, computable overlapping generations (OLG) model of economic growth that captures these interactions as well as of inter- and intra-generational health externalities. The model is then calibrated for a low-income country (Benin) and used to quantify the impact of a policy aimed at improving access to infrastructure on women's time allocation, growth and education and health outcomes. Implications of the analysis for strengthening the role of women in the growth process in developing economies are also discussed.Revised version November 2013
Keywords: J16; J22; O18; 330